Hadith Menyapu Muka Selepas Solat; Satu Kajian Analisis Sanad - Musa Bin Mohamad; Ahmad Bazli Bin Ahmad Hilmi; Abdel Rahman Ibrahim Suleiman; Wan Ahmad Zakry Bin Wan Kamaruddin (Kolej Universiti Islam Antarabangsa Selangor (KUIS), 2024)
Non-Indexed Publication